BIM-based integrated delivery technologies for intelligent MEP management in the operation and maintenance phase. (January 2018) - Hu, Zhen-Zhong; Tian, Pei-Long; Li, Sun-Wei; Zhang, Jian-Ping
Highlights: We proposed an approach to automatically establish the logic chain for MEP. We presented a set of solutions for as-built information creation and delivery. Intelligent O&M management of MEP was achieved in a novel heterogeneous platform. The platform was tested and successfully applied in a real project. Abstract: Incomplete building information in delivery and the lack of compatible tools for Operation and Maintenance (O & M) have hindered the development of the intelligent management of Mechanical, Electrical and Plumbing (MEP) systems. In fact, the information related to the O & M management of the MEP system conventionally comes from the completion documents in the forms of hard copies or unstructured digital files, making it hard to search for useful information in the "sea" of documents and drawings. Therefore, digitalization of information is an urgent task to facilitate the intelligent management of the MEP system. As a project deliverable, the as-built information model shall not only contain geometrical information and necessary construction-related data, but also built-in information useful for the intelligent O & M management. In the present study, based on the Building Information Modeling/Model (BIM) technology, a set of solutions including the automatic establishment of the logic chain for MEP systems, an equipment grouping and labeling scheme and an algorithm to transform BIM information to GIS map model, is proposed to digitalize and integrate the MEP-related information into the as-built model. Subsequently, a cross-platform O & M management system is developed using the MEP-related information in the as-built model to run routine O & M tasks and to effectively response to MEP-related emergencies. The developed system is applied to aid the O & M management of MEP engineering in a real project, showing that the developed system facilitates the intelligent O & M management and guarantees the security of the MEP system and its subsystems.